2018
DOI: 10.1002/epi4.12273
|View full text |Cite
|
Sign up to set email alerts
|

A single seizure selectively impairs hippocampal‐dependent memory and is associated with alterations in PI3K/Akt/mTOR and FMRP signaling

Abstract: SummaryObjectiveA single brief seizure before learning leads to spatial and contextual memory impairment in rodents without chronic epilepsy. These results suggest that memory can be impacted by seizure activity in the absence of epilepsy pathology. In this study, we investigated the types of memory affected by a seizure and the time course of impairment. We also examined alterations to mammalian target of rapamycin (mTOR) and fragile X mental retardation protein (FMRP) signaling, which modulate elements of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 37 publications
0
3
1
Order By: Relevance
“…Our results differ from a previous study with male C57BL/10J inbred mice, which have a greater prevalence of neocortical heterotopia and exhibit a lower seizure threshold to pentylenetetrazole (PTZ)-induced seizures (Gabel et al, 2013). While every experimental approach for seizure induction has its strengths and limitations, we used flurothyl in this study because of our extensive expertise with this approach (Lugo et al, 2014;Holley and Lugo, 2016;Holley et al, 2018;Binder et al, 2022). Moreover, flurothyl is much easier to use compared to methods requiring intraperitoneal injection, where mice often need multiple doses of chemiconvulsant to provoke a seizure or never exhibit a generalized seizure, complicating measures of latency.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Our results differ from a previous study with male C57BL/10J inbred mice, which have a greater prevalence of neocortical heterotopia and exhibit a lower seizure threshold to pentylenetetrazole (PTZ)-induced seizures (Gabel et al, 2013). While every experimental approach for seizure induction has its strengths and limitations, we used flurothyl in this study because of our extensive expertise with this approach (Lugo et al, 2014;Holley and Lugo, 2016;Holley et al, 2018;Binder et al, 2022). Moreover, flurothyl is much easier to use compared to methods requiring intraperitoneal injection, where mice often need multiple doses of chemiconvulsant to provoke a seizure or never exhibit a generalized seizure, complicating measures of latency.…”
Section: Discussioncontrasting
confidence: 61%
“…The chemi-convulsant flurothyl was used to induce an acute seizure as previously described by our group (Holley and Lugo, 2016;Holley et al, 2018). Each seizure was induced under a standard fume hood inside a clear acrylic (29 × 16 × 15 cm) inhalation chamber.…”
Section: Methodsmentioning
confidence: 99%
“…However, two points follow from our observations. First, Bernard et al [89] demonstrated in a normal rat model that early life seizures reduce dendritic FMRP at/near synapses, with a corresponding shift of FMRP to the neuronal soma, despite an apparent increase in overall hippocampal FMRP [90]. Thus, the occurrence of early-life seizure creates a functional deficit of FMRP for synaptic functioning in the rat, with the corresponding reduction of cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a portion of patients present with epileptic encephalopathy. On top of the disturbances related to the structural anatomy, epileptic activity causes memory consolidation disruption 29 and in epileptic brain there is a deviation from the optimal network organisation 30,31 . Cognitive disability is not only caused by epileptic activity or the underlying pathology, but also the use of anti-epileptic drugs has negative effects, due to general dampening of neuronal signalling and consequent detrimental effects on cognitive development 32 .…”
Section: Introductionmentioning
confidence: 99%